Singing to the goddess : poems to Kālī and Umā from Bengal - McDermott, Rachel Fell (Oxford University Press, 2001)
This collection presents 145 brief Bengali lyric poems dedicated to the Hindu goddesses Kali and Uma. These poems were written from the early-18th century up to the contemporary period. They represent the Bengali tradition of goddess worship (Saktism).